Implications for the introduction of earthworms in a biosolids amended agroecosystem - McDaniel, Jacob Philip, author; Barbarick, Kenneth, advisor; Stromberger, Mary, advisor; Cranshaw, Whitney, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: ammonium; trace metals; nitrate; Hydrus-1D